Strategi Manajemen Sumber Daya Manusia Dalam Pendidikan Islam: Pendekatan Berbasis Nilai Al-Qur’an Dan Sunnah - Anwari, Hamdan; Ali, Moh; Cahyani, Dewi (JURNAL MANAJEMEN PENDIDIKAN, 2025)
HUMAN RESOURCE MANAGEMENT STRATEGY IN ISLAMIC EDUCATION: AN APPROACH BASED ON THE VALUES OF THE QUR'AN AND SUNNAH This study discusses human resource management (HR) strategies in Islamic educational institutions with an approach based on the values of the Quran and Sunnah. The focus of the research is on human resource management that is able to improve institutional performance in a sustainable manner, by considering spiritual, moral, and professional aspects. The qualitative field research method was conducted at Mts Nurul Imaniyah, with data collection through observation and in- depth interviews. The research results show the importance of integrating the values of honesty, trustworthiness, justice, and Islamic work ethics in every stage of HR management, from planning, recruitment, training, to performance evaluation. This approach not only improves the professional competence of educators, but also shapes characters with noble morals and responsibility as caliphs on earth.